2013
DOI: 10.3354/ame01614
|View full text |Cite
|
Sign up to set email alerts
|

Responses of microbial food web to increased allochthonous DOM in an oligotrophic subarctic lake

Abstract: Climate-induced changes in catchment area vegetation and runoff alter the quality and quantity of carbon that enters lakes, with implications for food webs in recipient water bodies. The effect of dissolved organic matter (DOM) on the ratio between heterotrophic and autotrophic biomass and productivity was studied in a subarctic, clear water lake in northern Finland. In a mesocosm experiment, natural DOM from a subarctic bog and a boreal lake was added to the lake water, doubling the initial dissolved organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 76 publications
3
39
0
Order By: Relevance
“…Although DOC concentration has been identified as a main driver of interannual variations in oxygen content in other aquatic ecosystems, bacterial biomass and production in these peatland thaw lakes do not seem to be limited by organic carbon availability (Palmer et al 2014;Deshpande et al 2016). In humic lakes, it has been shown that high concentrations of DOC encourage a dominance towards chemoorganotrophic metabolic processes and away from autotrophic metabolic processes that would increase oxygen concentrations (Forsström et al 2013). This phenomenon has been consistently observed in humic lakes of northern Sweden when DOC concentrations were equal to or greater than 10 mg L −1 (Jansson et al 2000), as is the case for the peatland thaw lakes studied here (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DOC concentration has been identified as a main driver of interannual variations in oxygen content in other aquatic ecosystems, bacterial biomass and production in these peatland thaw lakes do not seem to be limited by organic carbon availability (Palmer et al 2014;Deshpande et al 2016). In humic lakes, it has been shown that high concentrations of DOC encourage a dominance towards chemoorganotrophic metabolic processes and away from autotrophic metabolic processes that would increase oxygen concentrations (Forsström et al 2013). This phenomenon has been consistently observed in humic lakes of northern Sweden when DOC concentrations were equal to or greater than 10 mg L −1 (Jansson et al 2000), as is the case for the peatland thaw lakes studied here (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…This provides substrates for bacterial heterotrophic production and also includes high concentrations of coloured dissolved organic matter (CDOM) that strongly attenuate light throughout the water column (Watanabe et al 2011), thereby reducing autotrophic phytoplankton production at depth (Shirokova et al 2009;Forsström et al 2013;Roiha et al 2015). Subarctic permafrost peatland lakes are favorable to both particle-based and free-living aquatic bacterial communities due to their high carbon and nutrient availability .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that DOM-enrichment increased heterotrophic metabolism, sometimes at the expense of autotrophic metabolic activity (Forsström et al, 2013). In an Arctic tundra lake of the Northwest Territories, addition of permafrost soil resulted in decreased bacterial production in the pelagic zone, but increased rates in the benthic zone (Moquin and Wrona, 2015).…”
Section: Controls On Bacterial Abundance and Productivitymentioning
confidence: 99%
“…The SAS waters lie directly on a peatland with palsas and therefore receive large quantities of organic matter as the palsas collapse into the ponds . In Scandinavian subarctic waters, addition of allochthonous DOC can stimulate bacterial production and abundance (Forsström et al 2013), which in turn could influence the rotifer growth and diversity. However, the dominant taxon of the SAS waters, P. euryptera, is known to be a selective feeder on larger prey items (Pourriot 1977).…”
Section: Zooplankton Diversitymentioning
confidence: 99%